EFFECT OF CORPORATE GOVERNANCE AND DISCLOSURE OF PROFITABILITY - ARDITYA, ARDITYA (Management, 2010)
In Indonesia, the issue of corporate governance is relatively new is still felt in recent years. Since the crisis, more and more are getting interested parties to discuss important aspects related to the business of creating a mechanism to manage the business based on the ways that ought to enable companies to run economically, effectively and efficiently so that it can deliver value to various parties who interested parties.Some of study that specifically examined the relationship between corporate governance structure with information disclosure has been made by Forker (1992), Ho and Wong (2000), and Sabeni (2002) in Khomsiyah (2003). The importance of research on corporate governance and disclosure of information can be viewed from two perspectives. The study was conducted to determine the application of the principles of corporate governance, given the important role of Corporate Governance in business management structure and a modern economy is sustained by capital markets and financial markets (Witherell, 2000; Oman, 2001 in Khomsiyah, 2003), increase public trust in companies (Brayshaw, 2002 in Khomsiyah, 2003).